Characteristics of Owners of Business on Strategic Access to Credit Facilities by Women Owned Small and Medium Enterprises (SMEs) - Mwirigi, Charles; Gakure, Roselyn Wangari; Otieno, Romanus Odhiambo (Advances in Social Sciences Research Journal, 2019)
The purpose of this study is to establish the characteristics of owners of Business on strategic access to credit facilities by Women owned small and medium enterprises (SMEs). The study adopted a descriptive research design guided by cross sectional survey. The target population was drawn from women owned enterprises specifically owners of businesses in Nairobi, Kenya. A sample of 370 was derived from the population. A pilot will be conducted to ascertain the validity and reliability of the instrument. Data collected from the respondents was captured in SPSS version 24 and analyzed using both descriptive and inferential statistics (correlation analysis and multiple regressions) to establish hypothesized relationships between the variables. The results were presented in form of tables, graphs, charts, means, standard deviations, t and f statistics. The findings of the study revealed that characteristics of business owners, collateral, networking and interest rates statistically and significantly predicts the Strategic access to credit SMEs owned by women (i.e., the regression model is a good fit of the data) and that interest rates significantly influence the Strategic access to credit SMEs owned by women in Kenya.